GAMBARAN WORK-FAMILY CONFLICT DAN STRATEGI COPING PADA DOSEN PRIA - Melani Aprianti; Ajeng Amalia (Fakultas Psikologi Universitas Tarumanagara, 2017)
To fulfil the demand of various roles undertaken to be a good father, as breadwinner and a role in the family, can be a pressure when it is inconsistent and conflicting between each roles. That kind of conflict is called the Work-Family Conflict. Given the importance of alignment between the work with the family, this study intends to get an idea of the form of conflict between work with the family (Work-Family Conflict) on male lecturers and strategies undertaken by them to resolve the conflict. The selection of two subjects aged 22 years to 52 years in this study was based on the results of research conducted by the Families and Work Institute in Lamanna, Riedman and Strahm (2012) which states that men with births between 1965 and 1994 largely had the view that family as important (family-centric). In order to get the full and total comprehension of the subject experience, the research design used in this study is qualitative research. This study reveals that as lecturers, both of the subject experienced conflicts where family interfering with work and work interfering with family. The dominant form of the conflict they have as lecturers are Strain based conflict and Time-Based Conflict. Most conflicts experienced by the subject whose wife is stay at home mom where the wife can’t fully understand the work situation. The coping strategies the subjects used are all forms of problem focused coping and emotion focused coping, except denial coping strategies where all the subjects admit the conflicts and keep thinking about those conflicts.Keywords: Work-family conflict , Coping stress, Male lecturers